2020
DOI: 10.3390/nano10101963
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Inorganic Nanoparticles to Direct Macrophage Polarization for Skeletal Muscle Regeneration

Abstract: Modulation of macrophage plasticity is emerging as a successful strategy in tissue engineering (TE) to control the immune response elicited by the implanted material. Indeed, one major determinant of success in regenerating tissues and organs is to achieve the correct balance between immune pro-inflammatory and pro-resolution players. In recent years, nanoparticle-mediated macrophage polarization towards the pro- or anti-inflammatory subtypes is gaining increasing interest in the biomedical field. In TE, despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…Consistently, an imbalanced M1 to M2 polarization impairs skeletal muscle repair (Kharraz et al, 2013 ). Interestingly, recent works have shown that some inorganic NPs such as gold, titanium oxide and cerium oxide NPs may act as immunomodulators, through a mechanism involving macrophage polarization (Corsi et al, 2020 ). Although further studies are necessary to address the therapeutic relevance of these nanosystems, they may represent a promising tool for skeletal muscle disorders ( Figure 4 ) .…”
Section: Nanocarriers As Drug and Gene Delivery Systems In Muscle Dis...mentioning
confidence: 99%
“…Consistently, an imbalanced M1 to M2 polarization impairs skeletal muscle repair (Kharraz et al, 2013 ). Interestingly, recent works have shown that some inorganic NPs such as gold, titanium oxide and cerium oxide NPs may act as immunomodulators, through a mechanism involving macrophage polarization (Corsi et al, 2020 ). Although further studies are necessary to address the therapeutic relevance of these nanosystems, they may represent a promising tool for skeletal muscle disorders ( Figure 4 ) .…”
Section: Nanocarriers As Drug and Gene Delivery Systems In Muscle Dis...mentioning
confidence: 99%
“…A study carried out by Raimondo and Mooney has reported that IL-4-conjugated gold NPs (AuNPs) are efficient in enhancing regeneration of murine skeletal muscle after ischemic injury via modulation of M2 macrophage polarization [ 54 , 70 ]. Ge and colleagues have also shown direct effects of bare AuNPs to stimulate macrophage repolarization for murine skeletal muscle regeneration [ 56 ]. Indeed, they reported that AuNPs significantly enhanced myogenic differentiation of myoblasts promoting in vivo regeneration in models of muscle defects in rats.…”
Section: Nps To Stimulate Tissue Repair and Regenerationmentioning
confidence: 99%
“…TiO 2 nanotubes have been reported to promote osteogenesis via crosstalk between macrophages and mesenchymal stem cells (MSCs) under oxidative stress, stimulation of M1 to M2 macrophage transition and reduction of early inflammation [ 56 ]. Mesoporous silica NPs (MSNs) have been employed to inhibit the inflammatory response and to enhance the osteogenic differentiation of bone marrow mesenchymal stromal cells (BMDMs) through their immunomodulatory effects on macrophages [ 57 ].…”
Section: Nps To Stimulate Tissue Repair and Regenerationmentioning
confidence: 99%
“…Consequently, an alternative line of research is based on the concept that the exclusive administration of cell secretome can harness cardiac endogenous repair pathways leading to both stimulation of angiogenesis and mitigation of inflammation and fibrosis [26]. Factors of cell secretome could also be incorporated into biomaterial-based microparticles that allow their prolonged release in order to extend the exposure time of the cardiac tissue [29,30] (Fig. 1).…”
Section: Cells As Therapeutic Agentsmentioning
confidence: 99%